The Fifth Freedom: Shaping EU Innovation Policy for Renewable Energy Storage and Decarbonization - Esmeralda Colombo (Energies)
This article proposes recognizing innovation as the European Union’s “fifth freedom”, alongside the free movement of goods, services, capital, and people, with the aim of embedding it into renewable energy legislation. Focusing on renewable energy storage—a critical but overlooked component of decarbonization—it identifies structural barriers in EU cleantech innovation, including regulatory fragmentation, slow financing, and weak industrial coordination. To address these, this article introduces the Risk–Resilience–Reward (RRR) framework, a strategic tool for more anticipatory policymaking. It outlines how the proposed Clean Energy Delivery Agency and Clean Energy Deployment Fund could operationalize the RRR framework to accelerate storage deployment and strengthen EU competitiveness. Embedding purpose-led principles in energy policy, this article positions storage as the “unsung hero of decarbonization” and offers takeaways for advancing a just, sustainable EU economy.